TİYATRODAN SİNEMAYA BRECHTYEN ESTETİĞİN İZİNDE: ASİYE NASIL KURTULUR. - İRİ, E. Candan (Turkbilig/Turkoloji Arastirmalari Dergisi, 2025)
The reflections of Brecht's aesthetics on Turkish theatre and cinema coincide with almost the same years. Keşanlı Ali Destanı, the first epic play of Turkish theatre, was adapted to the cinema with a similar approach as a result of the joint work of Haldun Taner and Atıf Yılmaz in 1964, when its first stage production took place. Brecht's aesthetics, which gained cinematographic representation in Turkey with this adaptation, continued its existence after a while with the addition of original productions alongside the adaptations. Atıf Yılmaz, who draws attention with his films that go beyond traditional cinema patterns, brings another epic work, Vasıf Öngören's play Asiye Nasıl Kurtulur, to the field of cinema in the same style, in addition to Keşanlı Ali Destanı. This play, which was previously made into a film with a traditional interpretation under the direction of Nejat Saydam, turns into a work where Brechtian approach is preserved through Yılmaz's interpretation. The aim of this study, which centers on Yılmaz's reinterpretation of Asiye Nasıl Kurtulur in the language of cinema, is to evaluate the adaptation in question within the framework of intertextuality-intersemiotics. In this context, firstly, the references of the adapting text to the original text have been brought into focus, and it was seen that the transfer from the play to the film was significantly faithful to the source work in terms of form and thematics. However, some changes/transformations, additions and deletions have also been made in the adapting work. Reproduced with these processes in accordance with the nature of cinema, Asiye Nasıl Kurtulur serves as a good example of the representation of Brecht's theatre, which is based on shaking the audience, in cinema. It can even be said that the film, in which epic features such as playfulness and alienation are increased, has moved to a line closer to Brechtian aesthetics compared to the play text taken as a model.